Basic Factors For Choosing A Place Of Muzaki Intention To Pay Zakat - Indah Septiana; Azwardi Azwardi; Ahmad Syathiri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
Muzakki's decision is that he is accustomed to paying zakat in formal institutions such as BAZNAS, LAZ, Dompet Dhuafa. or prefer to directly give to mustahiq. The research is limited and focused on the variables of income, education, consumption, and sharia corporate governance on muzakki's decisions in choosing a place to pay zakat in the city of Palembang. The research data uses secondary and primary data, secondary data to determine the total population and samples obtained from the Central Statistics Agency (BPS) while the primary data used in the 2021 period from November 01 to December 31, 2021 is used for data. The variables of this study were obtained by means of questionnaire observations and interviews. The analytical tool used in analyzing binary logistic regression. The findings of this study indicate that income is a determining factor in the decision to choose a place to pay zakat. Based on the partial test results, the income variable and Islamic Corporate Governance have a positive and significant effect on the decision to issue zakat. While consumption has a negative and significant effect on the decision to choose a place to issue zakat. Overall, the independent variables (income, education, consumption, sharia corporate governance) were able to explain the dependent variable (the decision to pay zakat) of 83 percent. The remaining 17 percent is explained by variables outside the model or other variables not studied.